(untitled) (Proceedings of Southern Federal University. Philology, 2015)
Bondareva Alexandra Dmitrievna The work has been done as part of linguistic source study and provides a comparative analysis of the two fragments of two descreptive books of the Solovetsky and Joseph Volokolamsky Monasteries in middle of the XVI century. The object of the study is articles of the icon inventory in terms of structure and content. The study has identified general and specific features of the monuments of the business literature, it is given the justification of linguacultural documents importance. Key words: descriptive book, article, form, form element, linguistic expression, comparative analysis, linguacultural content.